The international diplomacy of Israel's Founders : deception at the United Nations in the quest for Palestine / John Quigley. - Quigley, John B. (Cambridge University Press, 2016)
During the early to mid-twentieth century, the Zionist Organization secured a series of political victories on the international stage, leading to the foundation of a Jewish state and to its ability to expand its territorial control within Palestine. The International Diplomacy of Israel's Founders provides a revisionist account of the founding of Israel by exposing the misrepresentations and false assurances of Zionist diplomats during this formative period of Israeli history. By comparing diplomatic statements at the United Nations and elsewhere against the historical record, it sheds new light on the legacies of such leaders as Chaim Weizmann, David Ben Gurion, Abba Eban, and Shabtai Rosenne. Including coverage of little-discussed moments in early Israeli history, this book offers an important new perspective for anyone interested in the history of the Israeli-Palestinian conflict.